The impact of training & development towards employees’ performance in UMW Advantech Sdn Bhd (UASB) & Bahagian Pinjaman Perumahan (BPP) / Norshahirah Mohd Noor and Nurul Haslinda Nordin - Mohd Noor, Norshahirah; Nordin, Nurul Haslinda (2013)
Many organizations in the world desire for good performance in order to be aligned and named as world’s top successful organization. The success of an organization is not only depending on how well the firms can make profits. However, the employee’s performance is among the factors that determine on how do the organization can present itself in the industry. In order the meet the good quality of employee’s performance, training and development have taken place as the method to attract the employees to do job well. Numerous forms of training and development had been implemented by the organization either on the job or off the job. However, the training and development implement by the organization are questionable of how the practices are done, how effective the training and development program and the career development offer for the employees. Therefore, this study sought to determine the impact of training and development towards employee’s performance in UMW Advantech Sdn Bhd (UASB) which represent the private sector and Bahagian Pinjaman Perumahan (BPP) which represent the public sector. The study is randomly done to employees in both organizations. A questionnaire was designed to collect the data from both organizations. The results indicate that employee’s performance are associated with the training and development practices, effectiveness of training and development and career development offered for the employees. In conclusion, this study is aims to determine the relationship of all the factors with the employee’s performance in both organizations.